PENGARUH KEPEMIMPINAN, KARKTERISTIK PEKERJAAN DAN MOTIVASI TERHADAP KINERJA DENGAN MEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOUR PADA TVRI STASIUN JAWA TENGAH - Ristiana Triwik Mawati Dewi, 12.5202.0160 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to analyze the influence of Leadership, Job Characteristics, Motivation on the Performance of Organizational Citizenship Behaviour mediated at TVRI station employees in Central Java. Population which is the object of research is all employees in the organization by using purposive sampling method of sampling appropriate inclusion criteria were 120 respondents. The research instrument used by aquestionnaire using Likert scale. The techniquetestdata inthis studyincludestestinginstruments, testmodels, testhypothesesandtestmediation. The results showedthat theability ofthe modelin explainingthetrueleadership, job characteristics, andmotivationsarethe sameberrsamahavecontributed70.9% of the performance ofthe employees ofCentralJavaTVRI. While the remaining29.1% is explainedbyvariablesoutside the model. Research also shows that leadership does not affect the performance, while job characteristics, motivation and organizational citizenship behavior influence performance on TVRI station employees in Central Java Keywords: leadership, job characteristics, motivation, organizational citizenship behavior, performance.